2006
DOI: 10.1111/j.1742-6723.2006.00847.x
|View full text |Cite
|
Sign up to set email alerts
|

NexTemp thermometer can be used interchangeably with tympanic or mercury thermometers for emergency department use

Abstract: Based on temperature measurement only, the NexTemp thermometer can be used interchangeably with current mercury and tympanic thermometers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
6
0

Year Published

2008
2008
2021
2021

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 12 publications
2
6
0
Order By: Relevance
“…17 However, Fulbrook et al found that the use of chemical dot thermometer and tympanic membrane thermometer was not a reliable method in adult intensive care unit patients, 16 whereas Rajee and Sultana showed that chemical thermometers could be used instead of tympanic membrane thermometers in adults. 43 Our findings support the results of the study of Rajee and Sultana.…”
Section: Discussionsupporting
confidence: 90%
“…17 However, Fulbrook et al found that the use of chemical dot thermometer and tympanic membrane thermometer was not a reliable method in adult intensive care unit patients, 16 whereas Rajee and Sultana showed that chemical thermometers could be used instead of tympanic membrane thermometers in adults. 43 Our findings support the results of the study of Rajee and Sultana.…”
Section: Discussionsupporting
confidence: 90%
“…The chemical oral temperature modality was more precise than TM measurements when compared to oral (mercury measured) temperatures; with the chemical oral measurements within -0.6 to +0.5°C of oral (mercury in glass) temperatures as compared to TM measurements that ranged from -1.0 to +1.1°C (Rajee & Sultana, 2006). Using a chemical TA thermometer (Liquid Crystal Fever Temp Ultra®), the mean difference compared to oral (mercury in glass) temperatures was -0.077°C, compared to digital oral and oral (mercury in glass) temperatures (mean difference +0.049°C), and digital TM to oral (mercury in glass) temperatures (mean difference -0.015°C) in ED patients indicating chemical TA thermometry had less accuracy and precision than digital oral and digital TM temperatures as compared to oral (mercury in glass) temperatures .…”
Section: Chemical Thermometersmentioning
confidence: 97%
“…Oral chemical (Nextemp®) temperature measurements were compared to both oral (mercury measured) and TM temperatures in adult ED patients (Rajee & Sultana, 2006). The chemical oral temperature modality was more precise than TM measurements when compared to oral (mercury measured) temperatures; with the chemical oral measurements within -0.6 to +0.5°C of oral (mercury in glass) temperatures as compared to TM measurements that ranged from -1.0 to +1.1°C (Rajee & Sultana, 2006).…”
Section: Chemical Thermometersmentioning
confidence: 99%
“…Studies were conducted for febrile patients in emergency rooms (Nordås, Leiren, & Hansen, 2005;Rajee & Sultana, 2006;Varney, Manthey, Culpepper, & Creedon, 2002;Yaron, Lowenstein, & Koziol-McLain, 1995), geriatric inpatient wards (Christensen, Christensen, & Matzen, 1998;Prentice & Moreland, 1999;Smitz, Giagoultsis, Dewe, & Albert, 2000;Smitz, Van de Winckel, & Smitz, 2009), cardiovascular inpatient wards, neurosurgery inpatient wards, and cancer inpatient wards. Patient ages ranged widely, with participants from18 years of age to elderly people.…”
Section: Figure 1: Flow Diagram Of Article Selectionmentioning
confidence: 99%
“…Patient ages ranged widely, with participants from18 years of age to elderly people. The number of subjects per study ranged from 21 (Dzarr, Kamal, & Baba, 2009) to 213 (Nordås et al, 2005), with seven relatively large-scale studies involving more than 100 subjects (Christensen et al, 1998;Duberg, Lundholm, & Holmberg, 2007;Nordås et al, 2005;Rajee & Sultana, 2006;Smitz et al, 2009;Valle, Kildahl-Andersen, & Steinvoll, 1999;Yaron et al, 1995). Moreover, 73.3% of the studies were large-scale ones.…”
Section: Figure 1: Flow Diagram Of Article Selectionmentioning
confidence: 99%